Sinking bone flap with ipsilateral hemiparesis: the neurosurgical paradox—a case report and literature review - Pawan Goyal; Vishwa Bharathi Gaonkar; Aditya Gupta (Egyptian Journal of Neurosurgery)
Abstract Background One of the less known complications following cranioplasty is the sinking bone flap syndrome which usually occurs in patients with an accompanying ventriculo-peritoneal shunt which leads to intracranial hypotension. This condition is rarely seen in patients without a draining VP shunt. In this article, we describe the case of a patient who developed sinking bone flap syndrome without a VP shunt. Case presentation A 44-year-old gentleman with chronic liver disease developed altered sensorium following trivial falls and was diagnosed with an acute right fronto-temporo-parietal SDH for which he underwent decompressive craniectomy. Autologous cranioplasty was done three months following the procedure and patient was discharged with no deficits. He developed ipsilateral hemiparesis three years after cranioplasty and on evaluation was found to have a sinking bone flap. Redo cranioplasty was done with patient specific implant following which he improved neurologically. Conclusion Sinking bone flap syndrome can occur in the absence of VP shunt and patients should be regularly followed after cranioplasty to avoid development of neurological deficits.